PHENOTYPIC CHARACTERISTICS AND MORPHOLOGICAL SCORING OF KALIGESING ETAWA CROSSBRED GOATS IN LIVESTOCK CONTESTS - Ine Karni; Ica Ayu Wandira; Muhammad Dohi; I Nyoman Sadia; M. Ridwan Saedi; Luluk Lailatun Nurjanah (Universitas Muhammadiyah Malang, 2026)
Kaligesing Etawa Crossbred (PE) goats are local livestock with important value as genetic resources, contest animals, and potential breeding stock. This study aimed to describe the phenotypic characteristics and morphological scores of Kaligesing PE goats based on contest class and sex. The research was conducted in August 2025 in Mertak Tombok Village, Praya District, Central Lombok Regency, using a quantitative descriptive method with a field survey approach. The samples consisted of 34 male goats and 16 female goats with complete scoring data. The observed variables included head, ears, neck/dewlap, horns, body posture, hair coat, feet and legs, rewos, reproductive organs or mammary gland, tail, coat color pattern, overall body conformation harmony, and total score. Data were analyzed descriptively, while comparisons of total morphological scores were analyzed using one-way ANOVA and an independent sample t-test. The results showed that the total morphological scores of male goats ranged from 74.1 to 83.2, with the highest score observed in Class A. Meanwhile, the total scores of female goats ranged from 71.0 to 75.0, with the highest score observed in Class B. Statistical analysis showed no significant differences in total morphological scores among male classes, among female classes, or between male and female goats. Therefore, the observed variation represents descriptive morphological variation, and contest scoring can be used as a descriptive tool to evaluate the phenotypic quality of Kaligesing PE goats.